Competing in the Global Solar Photovoltaic Industry: The Case of Taiwan - Yu-Shan Su (International Journal of Photoenergy)
The top five solar cell supply countries in the world in sequential order are China, Taiwan, the United States of America, Japan, and Germany. The capacity of Taiwanese solar cell production is ranked top two in the globe. The competitive advantage of the Taiwanese electronics firms has facilitated the rapid developments to its solar photovoltaic industry. The Taiwanese solar photovoltaic industry possesses a large size and a complete value chain of upstream, midstream, and downstream sectors. In this study, I analyzed the trends and developments of the solar photovoltaic industry in Taiwan and in the globe. And I also investigated the positioning and competitive advantage of Taiwanese firms in the value chain of the global solar photovoltaic industry. I found that Taiwanese firms continue to have an important and indispensable role in the global solar photovoltaic industry by either differentiation or cost advantage.